The nonprofit sector : a research handbook - Powell, Walter W.; Bromley, Patricia (Assistant professor of education) (Stanford University Press, 2020)
"The third edition of The Nonprofit Sector, this handbook fills a unique space in the nonprofit literature as the only volume aimed at furthering research in the field. Since the last edition, which has remained a core text in the field, the nonprofit sector has evolved and now overlaps to a greater extent with business and government. The third edition highlights the growing role of nonprofits in public policy, current debates over the relationship between nonprofits and democracy, increasingly blurred lines between nonprofits and the market. Themes that remain highly relevant to the field--the history of the sector, the import of religion, the legal treatment of nonprofits--are again taken up in this new edition, but in all new contributions. The third edition features a nearly completely new group of authors. This third edition is not a mere update, but offers readers the cutting-edge of new research on the nonprofit sector"-- Provided by publisher
Keywords: Nonprofit organizations -- Management.; Nonprofit organizations.; Charitable uses, trusts, and foundations.; Organizations, Nonprofit; Associations sans but lucratif -- Gestion.; Associations sans but lucratif.; Fondations (Droit); nonprofit organizations.; Charitable uses, trusts, and foundations; Nonprofit organizations; Nonprofit organizations -- Management